2008
DOI: 10.1016/j.neuropsychologia.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping numerical cognition impairments in children with chromosome 22q11.2 deletion or Turner syndromes

Abstract: Children with one of two genetic disorders (chromosome 22q11.2 deletion syndrome and Turner syndrome) as well typically developing controls, participated in three cognitive processing experiments. Two experiments were designed to test cognitive processes involved in basic aspects numerical cognition. The third was a test of simple manual motor reaction time. Despite significant differences in global intellectual abilities, as measured by IQ tests, performance on the two numerical cognition tasks differed littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
106
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 47 publications
7
106
0
4
Order By: Relevance
“…With regard to non-numerical magnitude, some studies also found that people with 22q11DS had poorer performance when processing spatial and temporal continuous dimensions. Compared to age-matched controls, they were slower at comparing length (Simon et al, 2005;Simon et al, 2008), demonstrated less ability to reproduce rhythmic patterns as well as less sensitivity to temporal interval differences (Debbané, Glaser, Gex-Fabry, & Eliez, 2005;Gabriel Mounir, Debbane, Schaer, Glaser, & Eliez, 2011). These results 1 are consistent with the Theory of Magnitude proposed by Walsh (2003) who assumed the existence of a common metric system for representing number, space and time.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…With regard to non-numerical magnitude, some studies also found that people with 22q11DS had poorer performance when processing spatial and temporal continuous dimensions. Compared to age-matched controls, they were slower at comparing length (Simon et al, 2005;Simon et al, 2008), demonstrated less ability to reproduce rhythmic patterns as well as less sensitivity to temporal interval differences (Debbané, Glaser, Gex-Fabry, & Eliez, 2005;Gabriel Mounir, Debbane, Schaer, Glaser, & Eliez, 2011). These results 1 are consistent with the Theory of Magnitude proposed by Walsh (2003) who assumed the existence of a common metric system for representing number, space and time.…”
Section: Introductionsupporting
confidence: 82%
“…First, an impairment in all magnitude comparison tasks would suggest a generalized magnitude deficit for the processing of number, time and space, in keeping with the Theory of Magnitude proposed by Walsh (2003). A second pattern of result would show an impairment restricted to all numerical tasks (numerical magnitude judgment tasks) and would suggest a number sense deficit in accordance with the ANS view and with previous studies that already showed a less precise magnitude representation for symbolic and non-symbolic numerical stimuli in 22q11DS participants (Oliveira et al, 2014;Simon et al, 2008Simon et al, , 2005.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Their weakness does not emerge early in their arithmetical development as girls with TS show intact counting skills Murphy, Mazzocco, Gerner & Henry, 2006;Temple & Sherwood, 2002). Slow response times [RTs] have been reported but did not always reach statistical significance (Bruandet, Molko, Cohen & Dehaene, 2004;Simon et al, 2008;Temple & Sherwood, 2002).…”
Section: Girls With Ts Have Normal Intelligence With An Advantage On mentioning
confidence: 99%